As eleições legislativas de 1925 - Queiroz, António José (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The latest elections of the First Republic (November 8, 1925) were played in an atmosphere of great political turmoil, a situation that would not avoid the achievement of electoral agreements between some of the competing forces. In the end, as usual, the Portuguese Republican Party won. The election of deputies both of the Democratic Left and of the Union of Economic Interests was the novelty. In a global view, these elections can be considered “the most fraudulent and shameful” of the First Republic.